Strategic management accounting and performance implications: a literature review and research agenda - Jafar Ojra (SpringerOpen, 2021)
Abstract The important role that management accounting plays in driving organisational performance has been reiterated in the literature. In line with that importance, the call for more effort to enhance knowledge on strategic management accounting has increased over the years. Responding to that call, this study utilised a qualitative approach that involved a systematic review to synthesise existing literature towards understanding the strategic management accounting foundation, contingency factors, and organisational performance impact. Based on the evidence in reviewed literature, we flag key directions for advancing this theoretical premise towards providing further insights that would enable practitioners strategically align their strategic management accounting practices for optimal organisational performance. The limitations of this study have been acknowledged.